Informal roles within eSport teams : a content analysis of the game 'Counter-Strike: Global Offensive - Drenthe, Rolf (2016)
Informal roles are roles that are not formally prescribed by a group or organization and are being established through group interaction that takes place among group members. Previous literature has identified twelve roles within traditional sport, however to date limited research has been done within the field of role development within competitive computer gaming (eSports). The purpose of the present study was to explore the informal roles within the eSport setting and if it is possible to use audio analysis to identify informal roles. The present study is a qualitative, multiple case study of two professional eSport teams in the game ‘Counter-Strike: Global Offensive’. The data that was used was open source voice recordings of two professional eSport teams in the game ‘Counter-Strike: Global Offensive’. Abductive reasoning was used during the thematic analysis. The research used the twelve informal roles as initial codes, but during the study more codes derived from the data. A total of 19 codes were used in the end of the study. The findings of the present study suggest that roles such as the informal leader verbal and the distracter are commonly found. The enforcer was not found in the way as defined by previous literature, but as a person who enforces rules of the team, event and makes sure leaders tactics are followed. The cancer and comedian were found less common but were present. Roles such as the malingerer, social convener, star player and mentor were not found during the present study and it is suggested that these roles might be more likely to be found outside of matches. Communication characteristics such as interrupting, talking over each other, uncomprehending speech and high amount of words per minute are influencing the clear development of informal roles. It is possible that interrupting might be considered a new role (The interrupter) within sports that require, to the point clear communication.